The Effect of Glucagon-Like Peptide-2 Receptor Agonists on Colonic Anastomotic Wound Healing - Heather A. Redstone; William D. Buie; David A. Hart; Laurie Wallace; Pamela J. Hornby; Sarah Sague; Jen J. Holst; David L. Sigalet (Gastroenterology Research and Practice)
Background. Glucagon-like peptide 2 (GLP-2) is an intestinal specific trophic hormone, with therapeutic potential; the effects on intestinal healing are unknown. We used a rat model of colonic healing, under normoxic, and stress (hypoxic) conditions to examine the effect of GLP-2 on intestinal healing. Methods. Following colonic transection and reanastomosis, animals were randomized to one of six groups (n=8/group): controls, native GLP-2, long-acting GLP-2 (GLP-2- MIMETIBODY, GLP-2-MMB), animals were housed under normoxic or hypoxic (11%  O2) conditions. Animals were studied five days post-operation for anastomotic strength and wound characteristics. Results. Anastomotic bursting pressure was unchanged by GLP-2 or GLP-2-MMB in normoxic or hypoxic animals; both treatments increased crypt cell proliferation. Wound IL-1β increased with GLP-2; IFNγ with GLP-2 and GLP-2-MMB. IL-10 and TGF-β were decreased; Type I collagen mRNA expression increased in hypoxic animals while Type III collagen was reduced with both GLP-2 agonists. GLP-2 MMB, but not native GLP-2 increased TIMP 1-3 mRNA levels in hypoxia. Conclusions. The effects on CCP, cytokines and wound healing were similar for both GLP-2 agonists under normoxic and hypoxic conditions; anastomotic strength was not affected. This suggests that GLP-2 (or agonists) could be safely used peri-operatively; direct studies will be required.